2021
DOI: 10.3389/fimmu.2021.724464
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Metabolic Parameters Derived From 18F-FDG PET/CT for Microsatellite Instability in Patients With Colorectal Carcinoma

Abstract: BackgroundMicrosatellite instability (MSI) is one of the important factors that determine the effectiveness of immunotherapy in colorectal cancer (CRC) and serves as a prognostic biomarker for its clinical outcomes.PurposeTo investigate whether the metabolic parameters derived from18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) can predict MSI status in patients with CRC.Materials and MethodsA retrospective analysis was performed on CRC patients who underwent 18F-FDG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
6
8
0
1
Order By: Relevance
“…This is different from a recent study of Chung and colleagues [18] in gastric cancer, exhibiting that MSI-H tumors caused higher SUV max on 18 F-FDG PET/CT imaging, that may because gastric cancer with MSI-H tended to be larger-sized and histologically heterogeneous, which was different from colorectal cancer. We found a positive relationship between MSI status and MTV in colorectal cancer, which was in agreement with the previous findings [32]. Liu et al [32] retrospectively analyzed the pretreatment parameters of PET and reported the highest diagnostic performance of MTV in predicting MSI status in CRC despite its small sample size of 50 patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is different from a recent study of Chung and colleagues [18] in gastric cancer, exhibiting that MSI-H tumors caused higher SUV max on 18 F-FDG PET/CT imaging, that may because gastric cancer with MSI-H tended to be larger-sized and histologically heterogeneous, which was different from colorectal cancer. We found a positive relationship between MSI status and MTV in colorectal cancer, which was in agreement with the previous findings [32]. Liu et al [32] retrospectively analyzed the pretreatment parameters of PET and reported the highest diagnostic performance of MTV in predicting MSI status in CRC despite its small sample size of 50 patients.…”
Section: Discussionsupporting
confidence: 92%
“…We found a positive relationship between MSI status and MTV in colorectal cancer, which was in agreement with the previous findings [32]. Liu et al [32] retrospectively analyzed the pretreatment parameters of PET and reported the highest diagnostic performance of MTV in predicting MSI status in CRC despite its small sample size of 50 patients. However, the specific Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, an independent confirmatory study in a different, prospective, patient cohort would be required before any clinical recommendation can be made. MTV also demonstrated an association with overall survival, indicating potential prognostic value, as has been proposed in previous studies [35]. This might contribute to the diagnostic value of volumetric PET parameters in the future.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, ICIs showed clinical benefit only in patients with MSI (Le et al, 2015, André et al, 2020. Only two studies have reported the relationship between SUVmax and MSI in colon cancer, and these included a small number of patients with MSI, which showed no significant relationship between SUVmax and MSI (Li et al, 2021;Liu et al, 2021). In this study, the SUVmax of tumors with MSI was significantly higher than that of tumors with MSS.…”
Section: Relationship Between Suvmax and Msi And Kras Statusmentioning
confidence: 51%
“…The correlation between SUVmax and KRAS mutations has been assessed in several studies. However, these studies showed conflicting results and included a relatively small number of patients (Kawada et al, 2012;Chen et al, 2014;Krikelis et al, 2014;Kawada et al, 2015;Lee et al, 2016;Cho et al, 2017;Oner et al, 2017;Kim et al, 2019;Arslan et al, 2020) On the other hand, only two studies have reported the relationship between SUVmax and MSI in colon cancer, and these studies found no significant relationship between SUVmax and MSI (Li et al, 2021;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%